(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Background: Pregnancy ultrasound scans are beneficial in assessing and monitoring changes in the developing baby, solving issues, and guaranteeing the health of the mother and unborn child during pregnancy. Aim: This study aims to assess and determine of fetal and maternal health findings of those who underwent to prenatal ultrasound. Methodology: The data set comprised 81 pregnant women aged 25-40 years. All women underwent ultrasound examinations: one at 14-23 weeks of pregnancy and the other at 30-36 weeks. The examinations were conducted in different hospitals in Iraq over a period of one year between March 2023 and March 2024. The medical indicators and obstetric outcomes of mothers and fetuses were recorded. Results: A total of 81 pregnant women have a Prenatal Ultrasound. Current findings shown maternal with ages (31 – 35) years were the most common, which include 53.09% of total cases, where almost of maternal had a BMI (> 28.9 kg/m2) with 60 cases, smokers were 17 cases, Gestational age (37.0 – 40) weeks had 56.79% of pregnant women, fetuses death were 6.17%, severe morbidity was 3.70%. Limb abnormalities were found in 4.94% of total fetuses. Conclusion: The present article demonstrates that ultrasound is an effective technique in improving clinical outcomes for both maternal and fetal health.